The Effects of Economic Globalization on Indigenous Communities - Toti, Felix (International Journal of Humanity and Social Sciences, 2024)
Purpose: The general purpose of this study was to look into the effects of economic globalization on indigenous communities. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to economic globalization on indigenous communities. Preliminary empirical review revealed that economic globalization had diverse and often adverse impacts on indigenous livelihoods, cultures, and environments. It found that while some communities experienced short-term economic gains, many faced displacement, land dispossession, and environmental degradation. Additionally, the study highlighted the importance of recognizing and protecting indigenous rights, advocating for more inclusive and equitable development approaches. Collaboration between indigenous communities, governments, and civil society is crucial for addressing the challenges posed by economic globalization and promoting sustainable development that respects indigenous sovereignty and fosters social justice. Unique Contribution to Theory, Practice and Policy: World-Systems theory, Cultural Hybridity theory and the Dependency theory may be used to anchor future studies on economic globalization on indigenous communities. The study offered valuable recommendations that contributed to theory, practice, and policy in addressing the challenges faced by indigenous peoples. By synthesizing existing theoretical frameworks and advocating for culturally sensitive development policies, the study provided a comprehensive approach to understanding and addressing the impacts of economic globalization on indigenous livelihoods, cultures, and environments. The recommendations emphasized the importance of integrating indigenous knowledge, strengthening legal frameworks for indigenous rights protection, and fostering collaborative partnerships among diverse stakeholders. Overall, the study's recommendations aimed to empower indigenous communities, promote social justice, and advance a vision of sustainable development that prioritizes indigenous well-being.